Solution based zinc tin oxide TFTs: the dual role of the organic solvent. (13th January 2017) - Salgueiro, Daniela; Kiazadeh, Asal; Branquinho, Rita; Santos, Lídia; Barquinha, Pedro; Martins, Rodrigo; Fortunato, Elvira
Abstract: Chemical solution deposition is a low cost, scalable and high performance technique to obtain metal oxide thin films. Recently, solution combustion synthesis has been introduced as a chemical route to reduce the processing temperature. This synthesis method takes advantage of the chemistry of the precursors as a source of energy for localized heating. According to the combustion chemistry some organic solvents can have a dual role in the reaction, acting both as solvent and fuel. In this work, we studied the role of 2-methoxyethanol in solution based synthesis of ZTO thin films and its influence on the performance of ZTO TFTs. The thermal behaviour of ZTO precursor solutions confirmed that 2-methoxyethanol acts simultaneously as a solvent and fuel, replacing the fuel function of urea. The electrical characterization of the solution based ZTO TFTs showed a slightly better performance and lower variability under positive gate bias stress when urea was not used as fuel, confirming that the excess fuel contributes negatively to the device operation and stability. Solution based ZTO TFTs demonstrated a low hysteresis (Δ V   =  −0.3 V) and a saturation mobility of 4–5 cm 2 V −1 s −1 .